Pasaka kā mācību līdzeklis krievu valodas kā svešvalodas apguvē. - Semjonova, Jūlija (Latvijas Universitāte, 2009)
Mūsu diplomdarba tēma ir "Pasaka kā mācību līdzeklis krievu valodas kā svešvalodas apgu".Mēs izvēlējamies tieši pasaku tāpēc kā tā varētu palīdzēt skolēniem gan imācīties valodu, gan iepazistināties a r slaveno krievu kultūru un krievu mentālitāti.

The theam of our diploma work is "Fairytale as a Teaching Aid in Russian as a Foreign Language Lessons".Why we have chosen a fairytale like an object?Usually small children are studing the world when their parents read them fairytales, but we think that fairytales could helppupils to study Russian as a foreign language to know russian culture. How ti realise this pedagogical aim? Russian fairytales are very different and it is very interesting to work with them ! Pupils can make a theather and show drama by russian fairytales. They could make paper theather, where they are actors by themselves and scenarists. Children are speaking Russian and studing russian people's menthality. Every techer could use our work at their lessons.
Fairytale as a Teaching Aid in Russian as a Foreign Language Lessons
Keywords: Pedagoģija